Titanium nitrides as novel reactants for in-situ synthesis of TiB2-based composites with improved properties. (10th May 2023) - Zou, Ji; Liang, Huayue; Liu, Jingjing; Wang, Weimin; Zhang, Fan; Ji, Wei; Fu, Zhengyi
Abstract: A novel in-situ reactive approach based on the reactions among TiN, aluminum and boron has been developed to synthesize TiB2 -based composites including TiB2 - h BN (TB) and TiB2 - h BN-AlN (TBA). Fully dense ceramics with fine-grained microstructure were successfully obtained via spark plasma sintering at 1850 °C/60 MPa/5 min. Microstructure analysis suggests h BN flakes were homogenously distributed in the TiB2 matrix. For AlN, however, they were elongated into plate-like grains during sintering, in which lots of defects in terms of stacking faults and twinning structures were observed. The mechanical and thermophysical properties of as-sintered ceramics were comprehensively investigated and compared. Incorporating AlN significantly improved the flexure strength, hardness, fracture toughness and thermal conductivity of TiB2 - h BN ceramics. The electrical conductivity of TB (3.06 × 10 6 S/m) is larger than that of TBA (2.35 × 10 6 S/m) at room temperature, but the value (6 × 10 5 S/m) was lower than that of TBA (6.9 × 10 5 S/m) at 1173 K. Based on the measurement of electrical and thermal conductivity, electron and phonon contributions to thermal conductivities of TB and TBA were calculated and their temperature dependences were illustrated.